A homozygous missense variant in the homeobox domain of the NKX6‐2 results in progressive spastic ataxia type 8 associated with lower limb weakness and neurological manifestations. (16th April 2020) - Almatrafi, Ahmad; Umair, Muhammad; Eldardear, Amr; Al‐Luqmani, Majid; Hashmi, Jamil A.; Albalawi, Alia M.; Alfadhel, Majid; Ramzan, Khushnooda; Basit, Sulman
Abstract: Background: Progressive spastic ataxia is a heterogeneous disorder characterized by cerebellar ataxia and limb spasticity associated with other severe neurological complications. Spastic ataxia is classified into pure and complex types, inherited in both an autosomal recessive and autosomal dominant manner. It is caused by pathogenic variants in at least eight different genes, including NKX6‐2 (MIM 607063) located on chromosome 10q26.3. The present study aimed to identify the genetic variant(s) underlying progressive spastic ataxia and to establish the genotype–phenotype correlation. Methods: We collected a large consanguineous family having four affected individuals segregating progressive spastic ataxia in an autosomal recessive manner. To investigate the molecular cause of the disease, genomic DNA of three affected individuals underwent whole exome sequencing. Results: All of the affected individuals showed progressive clinical features such as spastic ataxia, lower limb weakness and other mild neurological abnormalities. Whole exome sequencing data were analyzed using different filters. Filtering of rare and shared homozygous variants revealed a novel homozygous missense variant (c.545C>T; p.Ala182Val) in a highly conserved homeobox domain of the NKX6‐2 protein. Conclusions: The findings of the present study add a novel variant to the NKX6‐2 mutation spectrum and provide evidence that homozygous variants in the NKX6‐2 cause progressive spastic ataxia associated with other abnormalities.